The influence of social media interactions on brand equity: A case of Old Mutual Zimbabwe - Maliti, Bright M (Midlands State University, 2020)
The development of social networks has transformed the communication landscape; companies are no longer co-creators of marketing information as consumers have been empowered to share their experiences with several online peers. After an economic melt-down, several financial service companies operating in Zimbabwe are facing hardships in regaining customer’s confidence and this has engendered transitory investments as well as under-capitalisation. This study aims to determine the influence of social media interactions on customer based brand equity within the context of financial services offered by Old Mutual Zimbabwe. The study will focus on evaluating the effects of various social media elements (user generated content, firm generated content and e-fluentials) on customer based brand equity constructs (including brand loyalty, awareness and brand image). Research study was guided by the following objectives; to determine the effects of firm generated content on brand awareness and to establish the effects of e-fluentials on brand image. In this study the researcher administered 50 questionnaires to customers and interviewed social media consultants for Old Mutual Zimbabwe so as to obtain contemporary data about the effects on social media interactions on customer based brand equity. Research findings indicated that, user generated content, firm generated content and e-fluentials significantly affect customer brand equity.